Desadaptation In Education - Adashova Farogat; Roziboyeva Barchinoy; Oymatova Dilorom Rozimurotovna (Euro Asian Journal Publishing, 2025)
This article presents ideas and considerations about the causes and consequences of maladaptive situations in education, as well as their psychoprophylaxis. One of the important issues facing the modern education system is ensuring the level of adaptation of students to study and the educational environment. When a student or pupil has problems with social and psychological adaptation to an educational institution, this condition is called maladaptation. This condition negatively affects not only individual development, but also the effectiveness of the entire educational process
Keywords: Maladaptation; new social environment; individual; subject